La responsabilité sociale des entreprises et les relations de travail : Effets juridiques - Rennard, Louisa (Université de Montpellier, 2019)
La responsabilité sociale des entreprises (RSE) est au cœur de nombreux débats relatifs aux sources du droit et à l’opposition entre droit souple et droit dur, que cette thèse a pour objet de dépasser afin d’analyser les réels effets juridiques produits par la RSE au sein des relations de travail. Souvent critiquée pour n’être que des normes autoproduites par les entreprises, sans réels effets juridiques, dans l’unique but d’empêcher l’action normative du législateur, la RSE est pourtant encouragée à l’échelle nationale et internationale car, à l’heure de la mondialisation, elle pallie les dysfonctionnements des normes sociales fondamentales et les limites territoriales des droits nationaux. Or, la RSE n’est pas dépourvue de tout effet juridique. En effet, les entreprises qui se créent leur propre ordre juridique privé en édictant diverses normes s’assurent parfois réellement de leur respect. Cette thèse démontre que la RSE ne doit pas être utilisée de manière subsidiaire aux droits sociaux fondamentaux et aux droits nationaux, mais de manière complémentaire. Cette complémentarité se manifeste dans un rapport de relevance juridique et un rapport de synergie entre les ordres juridiques privés d’entreprises et les autres ordres juridiques. Ainsi, cette réception des normes de RSE par les ordres juridiques étatiques permet de leur faire produire davantage d’effets juridiques et notamment d’engager la responsabilité des entreprises non respectueuses de leurs engagements envers les travailleurs. De plus, cette synergie permet au législateur de davantage s’approprier les pratiques des entreprises afin de réguler leur mise en œuvre et d’inciter les entreprises à développer une véritable politique de RSE, au point de procéder à un réel durcissement la RSE. Corporate social responsibility (CSR) is at the center of debates about law’s sources and the opposition between soft law and hard law, which this PhD work aims to overcome in order to analyse real CSR legal effects within labor relations. Often criticized for being only companies self-produced standards, with no real legal effect, for the sole purpose of preventing the legislator’s normative action, CSR is nevertheless encouraged at national and international levels because, at the globalization time, it overcomes the fundamental social standards dysfunctions and national rights territorial limits. However, CSR is not devoid of any legal effect. Indeed, companies that created their own private legal order by enacting various standards, sometimes ensure their own full compliance with it.Moreover, this PhD work demonstrates that CSR is no subsidiary way over fundamental social and national rights, but complementary. This complementarity shows in legal relevance and synergy between companies’ private legal orders and other legal orders. Thus, this receipt of CSR standards by national legal orders makes it possible for them to produce more legal effects, and in particular, to engage companies’ liability which don’t fulfil their commitments to workers. In addition, this synergy allows the legislator to better appropriate companies’ practices in order to regulate their implementation and encourage companies to develop a real CSR policy, to the point of proceeding to a real CSR hardening.
Keywords: Action en justice; Actions et défenses; Businessman; CSR; Effet juridique; Entrepreneurs; Legal action; Legal effects; RSE; Relations professionnelles; Responsabilité sociétale; Travailleurs; Workers

Vers une maîtrise du risque bancaire systémique - Maurin, Alexandra (Université Paris-Dauphine, 2019)
L'essor de la RSE, tant au sein des sociétés qu'au travers des concertations internationales, illustre l'importance qu'ont pris l'éthique et la morale dans les relations d'affaires. Le banquier y tient une place centrale puisqu'il est « le moteur de toutes les activités de son temps ». Du fait de son rôle prépondérant, aussi bien pour l'économie réelle que sur les marchés financiers, il devrait agir en précurseur du développement de la RSE. Pourtant, lors de la crise de 2007, l'incitation déraisonnée au surendettement des particuliers et le recours à la titrisation pour faciliter la diffusion d'actifs toxiques ont démontré une amoralité générale des banques dans la conduite de leurs affaires. De cette crise de grande ampleur ressortent des questionnements sur l’impact de l’aléa moral sur la stabilité des États et la volonté d’apporter des réponses juridiques au risque bancaire systémique, afin de responsabiliser les banquiers et d’éviter que l’Histoire ne se répète.
Keywords: Aléa moral; Banks' liability; Banque universelle; CSR; Corporate Social Responsibility; Crise économique; Droit des affaires; Economic crisis; Moral hazard; RSE; Responsabilité du banquier; Responsabilité sociétale; Responsabilité sociétale des entreprises (RSE); Risque financier; Risque systémique; Systemic risk; Universal banks

La réparation du dommage à l'environnement du fait des déchets simples en Côte d'Ivoire - N'guessan, Baudelaire (Université Côte d'Azur, 2019)
Les villes de Côte d’Ivoire à l’instar des capitales africaines sont constamment polluées par les déchets ménagers, les déchets des activités commerciales et artisanales, les déchets industriels non dangereux. Ces déchets simples dégradent l’environnement dans ses composantes naturelles à savoir, les sols, les eaux, l’air, la faune et la flore. La préoccupation essentielle n’est plus la constatation matérielle des dégradations environnementales, mais plutôt la réparation du dommage écologique causé par ces déchets. Sur quel fondement et selon quelles modalités le droit ivoirien pourrait-il réparer le dommage écologique ? Le droit ivoirien pourrait parvenir à la réparation du dommage écologique par une application coordonnée des règles de responsabilité civile de droit commun et celles de la responsabilité environnementale introduite par le code de l’environnement de 1996. Ce dispositif pourrait être renforcé par le mécanisme de la responsabilité élargie du producteur des déchets. Par ailleurs, la réparation en nature apparaît, à travers la remise en état, comme le mode de réparation à privilégier en matière de dommage écologique. Cependant, le législateur ivoirien devrait travailler à une reconnaissance claire du dommage écologique et à l’attribution de la personnalité juridique aux composantes de l’environnement en s’appuyant par exemple sur la cosmogonie africaine de la nature pour faciliter une réparation effective du dommage écologique. Cities in Côte d'Ivoire, like African capitals, are constant y polluted by household waste, commercial and craft waste and non-hazardous industrial waste. These simple wastes degrade the environment in its natural components, namely the soil, water, air, fauna and flora. The main concern is no longer the material recognition of environmental damage, but rather the repair of the ecological damage caused by these wastes. On what basis and in what ways could Ivorian law compensate for the ecological damage? Ivorian law could achieve compensation for ecological damage through thecoordinated application of the rules of civil liability under ordinary law and those of environmental liability introduced by the 1996 Environmental Code. This mechanism could be strengthened by the mechanism of extended producer responsibility for wastes. In addition, compensation in kindappears, through rehabilitation, to be the preferred method of compensation for environmental damage. However, the Ivorian legislator should work towards a clear recognition of ecological damage and the attribution of legal personality to the components of the environment, for example by relying on the African cosmogony of nature to facilitate effective compensation for ecological damage.
Keywords: CSR; Côte d'Ivoire; Dommage écologique; Déchets; Ecological damage; Environment; Environnement; Infractions contre l'environnement; RSE; Responsabilité environnementale; Responsabilité pour dommages à l'environnement; Waste

Droit minier et droits des populations rurales en matière foncière et environnementale en Côte d'Ivoire - Douzouo Doman, Debatoh Solange (Université Félix Houphouet-Boigny, 2019)
L’étude de l’histoire du droit minier en Côte d’Ivoire nous révèle que la problématique foncière et environnementale est inhérente à l’exploitation minière en zone rurale. En effet, depuis la période coloniale jusqu’à nos jours, le droit de détruire au nom du développement prévaut sur les intérêts fonciers et environnementaux des populations rurales. L’envergure des impacts sociaux et environnementaux découlant des projets miniers nous amène à nous interroger sur la pertinence du cadre juridique encadrant l’activité minière. Quelle est l’efficience d’un cadre juridique qui sacrifie les acquis fonciers et environnementaux d’un peuple au profit d’un développement économique ? Un cadre juridique qui légalise « le droit de détruire » et fait échec aux politiques de sécurisation foncière et environnementale du même État ? Le caractère d’utilité publique suffit-il à justifier les impacts nocifs de l’extractivisme, grevant ainsi l’avenir au bénéfice du présent ? Bien que l’objectif poursuivi par le législateur au fil de l’histoire du droit minier ait toujours été de créer un cadre juridique attrayant pour les investisseurs étrangers, le Droit minier au-delà de cet objectif est devenu un facteur d’instabilité juridique en zone rurale. En contrepartie des richesses et des emplois promis par l’industrie minière, les populations ont dû payer un « prix social » hautement élevé. Quelles solutions juridiques pourraient permettre de garantir les droits des populations rurales dans la gouvernance minière en zone rurale ? Au vu des résultats de nos recherches, il ressort qu’il doit être mis en place un Droit minier fédérateur des intérêts de toutes les forces en présence, à savoir autant l’Etat et l’exploitant minier que le paysan ou le propriétaire foncier dans l’exploitation minière en zone rurale. Bien que les exploitants miniers possèdent un permis d’exploiter, cela semble ne pas être suffisant pour l’exploitation minière en zone rurale. Il faut y ajouter « un permis social d’exploiter ». La prise en compte des intérêts fonciers et environnementaux des populations rurales dans la mise en œuvre du droit minier doit constituer un préalable à l’exploitation minière en zone rurale. Cela contribuera à une bonne gestion foncière et environnementale dans la gouvernance minière en zone rurale.
Keywords: Bonne gouvernance; Comité de Développement Local Minier; Droit colonial; Droit minier; Droits des peuples; Développement durable; EIES; Environnement; Exploitation minière; Foncier; Orpaillage clandestin; Permis social; Sécurisation foncière

La place des entreprises transnationales dans les processus de justice transitionnelle en RDC et en RCA - Ngueuleu Djeuga, Isidore Collins (Université Paris Cité, 2019)
Le débat qui existe depuis les années 1970 sur l'absence ou la nécessité d'un instrument juridique internationalement contraignant, chargé de réguler l'impact des entreprises transnationales sur les droits humains, n'a pas suffisamment pris en compte la problématique des graves crimes économiques commis pendant les conflits armés. En République Démocratique du Congo (RDC) comme en République Centrafricaine (RCA), des entreprises transnationales notamment extractives, ont été accusées de pillages de ressources naturelles et de complicité dans la commission de graves crimes. Pourtant au niveau national comme au niveau international, le cadre juridique actuel est faible et déficitaire encourageant ainsi une culture de l'impunité à l'égard d'acteurs jouant un rôle important dans les conflits contemporains. Même si le droit international humanitaire est directement opposable aux acteurs non-étatiques dont les entreprises transnationales, son applicabilité demeure pour l'instant théorique car le droit international pénal et l'ensemble des tribunaux pénaux internationaux créés depuis le procès de Nuremberg se sont limités à juger les personnes physiques. Si certains auteurs y voient une opportunité et surtout importante pour faire évoluer le droit international, il ne faut surtout pas négliger les obstacles importants constitués de nombreux enjeux qui visent non seulement à sauvegarder l'exclusivité de l'État comme sujet du droit international mais aussi les intérêts économiques qui découlent de l'activité commerciale en période de conflit. C'est pour répondre à cette situation que l'option de la justice transitionnelle est étudiée dans cette thèse. Sans être un nouveau droit, elle permet une utilisation stratégique du droit existant afin de réconcilier l'obligation de faire justice et les intérêts économiques des entreprises. Elle profite d'un moment d'exception favoriser la mise en oeuvre de mesures exceptionnelles difficilement réalisable en temps de paix, telles que des tribunaux spéciaux ou des Commissions vérité et réconciliation. La combinaison de mécanismes judiciaires et non judiciaires rend donc in fine possible la responsabilité des entreprises pour leur complicité dans la commission des graves crimes notamment économiques. The debate that has existed since the 1970s on the absence or the need for an internationally binding legal instrument to regulate the impact of transnational corporations on human rights has not sufficiently taken into account the problem of serious crimes economic committed during armed conflicts. In the Democratic Republic of Congo (DRC) and the Central African Republic (CAR), transnational companies, including extractive companies, have been accused of complicity in committing serious crimes including looting natural resources. Yet at the national and international levels, the current legal framework is still weak and deficient, thus fostering a culture of impunity for such actors playing an important role in contemporary conflicts. Although international humanitarian law is directly opposable to non-state actors, including transnational corporations, its applicability remains theoretical for the moment, since international criminal law and all the international criminal tribunals created since the Nuremberg trial have been limited to judge natural persons. While some authors see it as an opportunity for the evolution of international law, we must not neglect the important obstacles that aim not only to safeguard the exclusivity of the State as a major subject of international law but also the economic interests that flow from commercial activities in times of conflict. It is to answer to this situation that the option of transitional justice is studied in this thesis. Without being a new law, it allows the strategic use of existing laws to reconcile the obligation to do justice and the need to preserve business attractivity. It takes advantage of an exceptional moment to encourage the implementation of exceptional measures that are difficult to achieve in peacetime, such as special tribunals or Truth and Reconciliation Commissions. The combination of judicial and non-judicial mechanisms ultimately makes it possible for companies to be accountable for their complicity in the commission of serious crimes including economic crimes.
Keywords: Accountability; Complicity; Complicité; Crimes économiques; Droits de l'Homme; Economic crimes; Entreprises multinationales; Entreprises transnationales; Hard law; Human rights; Justice transitionnelle; Natural resources; Responsabilité; Ressources naturelles; République Centrafricaine; République Démocratique du Congo; Soft law; Transitional justice; Transnational corporations

Corporate Social and Environmental Reporting in OHADA Context: Evidence from Companies Listed on the Douala Stock Exchange - Nganthou, Alexis; Boukar, Hamadou; Djeugou, Gaelle (Research Journal of Finance and Accounting, 2019)
This research questions the capacity of the OHADA accounting system to report on the societal commitment of companies. To carry out such a study, we are interested in the companies of the Douala Stock Exchange, which permanently publish green operations. The analysis was done at two levels: the first level of analysis highlighted the categories of green operations reported by the companies of our sample. The second level of analysis consisted in analysing the financial statements produced by these companies, in order to see in which accounts green transactions are recorded. The analysis reveals that, apart from some additional clarifications to be made in the appendices, the financial statements produced according to OHADA do not specifically highlight green information.
Keywords: Carry (investment); Green operations; Publication; Sample (material); Societal commitment; Stock (firearms)

Firmes TIC et responsabilité sociétale des entreprises en Afrique, cas du congo - Bokilo Lossayi, Julien (Revue Africaine et Malgache de Recherches Scientifiques : Sciences juridiques et politiques, 2019)
L’analyse des enjeux de la responsabilité sociétale des entreprises (RSE) des firmes TIC en Afrique se fait en tenant compte du degré de structuration de chaque Etat (démocratique ou non) qui en influence la forme et détermine le type de RSE. Partant du postulat selon lequel la RSE peut être le palliatif d’un Etat défaillant, l’objectif de cette étude est d’analyser l’impact sur les populations pauvres et vulnérables des politiques sociétales des firmes. L’enjeu scientifique de cette analyse, à partir d’études de cas africains, et du Congo en particulier, est aussi de réfléchir sur l’ambivalence de l’impact des politiques sociales des firmes TIC en Afrique, afin de montrer l’opportunité qu’offre le développement exponentiel des nouvelles technologies de la téléphonie dans la mise en oeuvre des politiques sociales dans ces pays. Aussi, en filigrane, ce travail questionne la prise en compte, dans les politiques relatives à la RSE de ces firmes, des conséquences du processus de production des consommables et accessoires TIC sur les populations, en l’occurrence les jeunes enfants travaillant dans les mines. Analysis of the issues of the corporate social responsibility (CSR) of the ICTs in Africa companies is done taking into account the degree of structuring of each State (Democratic or not) which influence the form and determines the type of CSR. Starting from the premise that CSR can be the palliative of a failed State, the objective of this study is to analyze the impact on poor and vulnerable people of firm’s societal policies. The scientific issue of this analysis, based on studies of African cases, and the Congo in particular, is also to reflect on the ambivalence of the impact of social policies of the ICTs firms in Africa, in order to show the opportunity that offers exponential development of NICTs in implementation of social policies in these countries. Also, implicitly, this work questions taking into account, in policies on CSR of these firms, of the consequences of the process of production of consumables and accessories ICT on populations, in this case young children working in the mines.
Keywords: CSR; Congo; Corporate Social Responsibility; ICT; RSE; Responsabilité sociale des entreprises; Responsabilité sociétale; TIC

L'entreprise sobre : essai sur un concept juridique émergent - Baudouin-Feig, Valentin (Université de Strasbourg, 2019)
L'entreprise est une liberté ambigüe, elle est autant un facteur de progrès que de risque. La crise écologique actuelle conduit les entreprises à prendre conscience des effets de leurs activités sur la société dans son ensemble et l'environnement. Pressées par de nouvelles normes sociales de la société civile, les entreprises sont amenées à modifier leur comportement, notamment à travers une démarche de responsabilité sociétale et environnementale. C'est alors la société commerciale - enveloppe juridique de l'entreprise, non définie par le droit quant à elle - qui est interrogée dans sa définition et sa fonction sociale. En témoigne la récente réforme du contrat de société commerciale pour y intégrer la prise en compte d'enjeux sociaux et environnementaux. C'est surtout l’adoption d'engagements volontaires qui participe d’une modification de la société commerciale à travers l’élaboration par des personnes de droit privé, de normes de droit souple, c’est-à-dire dénuées de la contrainte. Phénomène qualifié de droit post-moderne, les engagements volontaires amènent l'entreprise à hisser son comportement standard à un degré de responsabilité supérieur au droit "de lege lata", permettant éventuellement d’aboutir à l'engagement de sa responsabilité juridique par l’introduction d’une action en justice. Aussi, le développement des formes sociétaires de l'économie sociale et solidaire et l’apparition de sociétés inspirées de modèles étrangers sont une première brèche dans l'approche classique de la société commerciale. Constatant l'insuffisance de la RSE et des formes sociétaires de sociétés commerciales responsables à prendre véritablement en considération les enjeux environnementaux, il est proposé de conceptualiser une « entreprise sobre ». Un travail de réflexion sur la sobriété, concept juridique émergent, est effectué à partir de la terminologie déjà présente dans la législation. La définition juridique de la sobriété et plus précisément, ce qui constitue un comportement sobre doit permettre de fournir une aide à l'intégration de l'environnement dans l'entreprise. Ou pour le juge, de caractériser le standard juridique du comportement sobre. Des instruments de caractérisation d'un comportement sobre sont envisagés à travers une relecture des éléments du contrat de société commerciale (associé, apport, bénéfice, objet social et intérêt social). Ces développements soulevés à l’appui d'une dynamique de changement de la société commerciale, doivent permettre de mettre en exergue la nécessité de définir l’entreprise à partir de sa fonction sociale et comme un système en vue de satisfaire des intérêts communs.
Keywords: CSR; Commercial company; Ecological transition; Enterprise; Entreprise; Environnement; RSE; Responsabilité sociétale; Sobriety; Sobriété; Société commerciale; Transition écologique

La Responsabilité Sociétale des Entreprises (RSE), élément de financement pour la protection sociale au Sénégal - Adame, Kossi (Université Cheikh Anta Diop, 2019)
Keywords: CSR; Protection sociale; RSE; Responsabilité sociétale de l'entreprise; Sénégal

9 Necesarios debates sobre La Responsabilidad Social: 87 reflexiones de expertos - Durán, David Lafuente; García, Juan José Almagro; Franco, Helena Ancos; Ruiz, Antonio Argandoña; García, Irene Bajo; Maestre, Miwi Clavera; Cedillo, Carlos Cueto; Pérez, Bernabé Escobar; Rodríguez, María del Mar Miras; Monteros, Carlos Espinosa de los; Romero, Celia Ferrero; Zazo, José Ignacio Galán; et al. (Comares, 2019)
Llevamos años hablando de responsabilidad social, de compromisos, de crecimiento, de respeto, de integración ¿qué papel desarrolla hoy la responsabilidad social? ¿hablamos de una moda pasada? ¿una quimera inanimada llamada a languidecer?La presente obra es un compendio de reflexiones, análisis, puntos de vista y meditaciones en primera persona, por parte de los mejores profesionales de la responsabilidad social en nuestro país. Una obra colectiva que pretende ser punto de partida para quienes se inician en el estudio y análisis de la responsabilidad social, así como complemento a todos aquellos doctos en la materia que desean conocer las últimas tendencias y estudios de los principales protagonistas.El texto recoge la participación de los principales académicos que llevan años reflexionando sobre la materia, de políticos de diversa tendencia y orientación ideológica, de líderes empresariales y profesionales de la comunicación, de las más activas asociaciones y grupos de interés que están liderando las principales iniciativas vinculadas a la responsabilidad social, así como de los funcionarios y administraciones públicas más implicadas en su desarrollo.Las aportaciones se vertebran en torno a diez ejes de análisis, que van desde la delimitación y alcance del término hasta las líneas futuras de desarrollo, pasando por el examen de los principales ejes en los que se circunscribe: la ética y el buen gobierno, el respeto por los derechos humanos, el compromiso medioambiental, la inclusión de la ciudadanía, la necesaria comunicación o el imperativo reflejo en la cuenta de resultados.Una lectura amena y pausada que pretende poner sobre la mesa las líneas de reflexión y desafíos más actuales a los que se enfrenta la responsabilidad social en nuestros días y a los que se enfrentará en un futuro próximo.
Keywords: Responsabilidad Social

Shareholder activism, corporate social responsibility and financial performance - Yang, Yi (Victoria University of Wellington, 2019)
The thesis examines the influence of shareholder activism on corporate social responsibility (CSR) disclosure of targeted firms and its spillover effects on CSR disclosure, corporate social performance (CSP) and financial performance (FP) respectively in peer firms. The research is motivated by filling the research gaps in prior literature and providing insights to shareholders, the management and regulatory bodies in practice. The thesis consists of three parts. Firstly, this thesis reviews the literature surrounding shareholder activism by conducting narrative reviews of 92 working papers and publications and meta-analysis on 55 working papers and publications, published during 2000-2017 period. Theories from prior literature, namely agency theory, stakeholder theory and stakeholder salience theory are analysed through narrative review analysis at the beginning of the chapter. Then, the analysis of narrative review also documents mixed findings of the associations among shareholder activism and FP and CG and CSP, including spillover effects. That is, the associations could be positive, negative and not significant in prior literature. The results of meta-analysis indicate that shareholder activism improves FP and CSP respectively. In addition, the thesis also examines the major types of shareholder activists and main forms of shareholder activism. Overall, through the analysis, the thesis identifies the research gaps of prior literature, thereby pointing out future research directions. Secondly, by employing shareholder proposals from Standard & Poor's 1,500 (S&P 1,500, hereafter) companies in the United States as a proxy of shareholder activism during 2006-2014 period with 13,572 separate observations, this thesis examines whether the whole sample of shareholder activism, institutional shareholder activism and coordinated shareholder activism could influence CSR disclosure level respectively. Simultaneously, this thesis also investigates whether shareholder activism affects CSR disclosure level given the other corporate governance mechanisms, namely board size, the presence of female directors, outside directors and CEO incentives. The results typically demonstrate that: (1) while shareholder activism negatively relates to CSR disclosure level, larger board size or the presence of female directors combined with shareholder activism directly relates to maintaining better CSR transparency; (2) coordinated shareholder activism could decrease social disclosure level. The findings also indicate that CSR disclosure provides an approach to strategically manage risks. Thirdly, the thesis explores spillover effects from different types of shareholder activism on CSR disclosure level, CSP and financial performance by using data gathered from S&P 1,500 companies during 2007-2014 period. The findings show that shareholder activism increases social disclosure level and environmental disclosure level in peer firms. It also shows that there is a weak positive association between shareholder activism and CSP. It therefore demonstrates the weak influences of shareholder activism in changing firms’ CSP. It also illustrates that institutional shareholder activism has an advantage over coordinated shareholder activism in terms of increasing corporate transparency. In this manner, it indicates that the collective action problem among coordinated shareholders could also attenuate the impact of shareholder activism in peer firms. The thesis contributes to the literature on shareholder activism practically and theoretically. The findings provide useful insights to shareholders, management teams and regulatory bodies for their policy-making. Beyond the practical contribution, the thesis also provides empirical evidence to stakeholder salience theory and analyses the collective action problem.
Keywords: CSR disclosure; Corporate Social Responsibility; Corporate governance; Corporate social performance; Financial performance; Shareholder activism

Empresas transnacionais e direitos humanos : desafios jurídicos e sociais a partir do direito internacional - Wünsch, Marina Sanches (Universidade Federal do Rio Grande do Sul, 2019)
As empresas transnacionais, atualmente, são responsáveis por uma parcela significativa dos fluxos de capital no mundo, uma parte disso através do investimento estrangeiro direto (IED). Como resultado, elas são consideradas pelos países em desenvolvimento, como o Brasil, um meio importante de alcançar o desenvolvimento. O anseio desses países em atrair essa forma de investimento permite que estas grandes empresas adquiram alto poder de pressão político e econômico e, consequentemente, poder sobre as regulações, assim como no cumprimento de normas de proteção aos Direitos Humanos (DH). Este cenário apresenta um desafio sem precedentes no campo do Direito Internacional (DI), que se expressa na divisão em duas correntes principais no âmbito de discussão sobre Empresas e Direitos Humanos. Existem aqueles cuja defesa centra-se nos Princípios Orientadores das Nações Unidas sobre Empresas e Direitos Humanos, considerado como o principal instrumento hoje na área, porém se trata de uma regulação de soft law. Há aqueles que propugnam a defesa de um instrumento de hard law com a elaboração de tratado vinculante sobre Empresas e Direitos Humanos. Além disso, destaca-se um movimento por parte das próprias empresas em adotar mecanismos de Responsabilidade Social Corporativa (RSC). Diante desse cenário, a presente tese apresenta o seguinte problema: Qual é o efetivo papel que o Direito Internacional pode desempenhar na relação entre Empresas Transnacionais e Direitos Humanos, diante de suas bases estruturais e marcos regulatórios? O objetivo geral da tese é discutir o papel do Direito Internacional nesta relação ETNs e DH e analisar se o DI contribui ou pode contribuir para uma efetiva proteção às vítimas de violações de DH praticadas por essas empresas. Para dar conta disso, esta tese apresenta uma abordagem crítica do DI e uma perspectiva histórica. Em termos metodológicos, a presente pesquisa é de caráter qualitativo, assentada no método dialético de abordagem. Para desenvolver a pesquisa foram escolhidos três procedimentos técnicos de coleta de dados: revisão bibliográfica, análise documental e estudo de caso. Com relação ao estudo de caso, a escolha recai sobre o rompimento da barragem das empresas Samarco, Vale e BHP Billiton em Bento Rodrigues, distrito da cidade de Mariana/MG, pois este representa um dos inúmeros casos de empresas acusadas de violarem direitos humanos. Além disso, o caso ocorreu no Brasil e as empresas adotavam mecanismos de Responsabilidade Social Corporativa. Como principais contribuições, esta tese expõe a histórica e estreita relação entre Estado, Empresa privada e DI, sendo essa uma das principais razões que dificultam a elaboração de um instrumento vinculante sobre Empresas e Direitos Humanos. Ademais, evidenciou-se que tanto o movimento de Responsabilidade Social Corporativa quanto os Princípios Orientadores das Nações Unidas sobre Empresas e Direitos Humanos situam-se dentro do marco neoliberal e reforçam esse modelo, que privilegia a proteção da propriedade em detrimento de outros interesses. Ao final, o trabalho apresenta alguns pressupostos sob os quais se deve assentar uma proposta que preencha as lacunas identificadas nos debates atuais e oferecer contribuições para que esses pressupostos possam ser instrumentalizados na prática.
Keywords: CSR; Corporate Social Responsibility; Direito internacional; Direitos humanos; Empresa multinacional; Human rights; International law; Neoliberalism; RSE; Transnational corporations

Corporate Governance and Corporate Social Responsibility - Guidoux, Aymeric (Université Paris-Saclay, 2018)
Selon la théorie des parties prenantes, la Responsabilité Sociétal de l’Entreprise (RSE) est la réponse donnée par les entreprises à la pression croissantes des employées, actionnaires, communautés locales, ONG environnementales ou régulateurs afin de prendre en compte les impacts environnementaux et sociaux de leurs activités. L’enjeu n’est pas une simple compensation des externalités négatives mais une transformation des entreprises pour permettre une croissance durable. Ainsi, la RSE pousse les entreprises à être proactive et à dépasser les attentes règlementaires. Cependant, comment réussir à concilier des objectifs si différents voire opposés ? Alors que de plus en plus d’entreprises intègrent la RSE au cœur de leurs stratégies, les processus de gouvernance semblent être le chainon manquant pour réunir performance économique, sociale et environnementale. Cette thèse présente des arguments empiriques et théoriques de l’impact de la gouvernance à son plus haut niveau, du conseil d’administration au Directeur Général (DG). Après un chapitre d’introduction, le chapitre 2 analyse le lien entre la composition des conseils d’administrations et l’intégration de la RSE dans la stratégie des entreprises. Il s’appuie sur une loi sur la représentation des femmes dans les conseils d’administrations. Adopté en France en 2011, cette loi a entrainé la nomination de nouveaux administrateurs, majoritairement des femmes plus jeunes que leurs prédécesseurs. Pour autant, ce chapitre montre que l’augmentation de la diversité au sein des conseils n’est pas corrélée à variation de la performance financière et extra-financière. Ce chapitre repose sur l’étude des entreprises du SBF 120 de 2009 à 2015. Cependant, si les caractéristiques des administrateurs sont impliquées dans les processus de décisions, la mise en place des stratégies et le management de l’entreprise est confié au soin du DG. Grâce à un système de rémunération avec part variable, le conseil d’administrations s’applique à aligner les intérêts du DG avec les siens. Le chapitre 3 étudie l’efficacité des rémunérations variables basées sur des critères environnementaux ou sociétaux. Il montre que l’impact de ces « Bonus RSE » dépend du modèle de gouvernance de l’entreprise. Chez les entreprises possédant une gouvernance de type actionnarial, les « Bonus RSE » semble n’avoir qu’un impact négatif sur la performance financière. En revanche, pour les entreprises du type partenarial, ces bonus permettent efficacement l’amélioration des performances extra-financières sans diminuer la performance financière. Cette étude empirique se base sur un panel mondial de 3500 entreprises sur la période 2006-2015. Le chapitre 4 propose un modèle théorique permettant d’analyser l’impact de la nature intrinsèque ou extrinsèque des motivations. Basé sur le modèle principal-agent développé par Che et Yoo (2001), ce chapitre analyse différentes incitations pour une entreprise composée de deux agents travaillant sur une tâche « RSE ». Trois scénarios sont étudiés : les deux agents reçoivent une compensation financière, les deux agents sont motivés intrinsèquement, un agent est motivé intrinsèquement et l’autre financièrement. Le modèle montre que le scénario optimal pour le principal dépend du niveau de motivation intrinsèque mais également de l’interdépendance entre les décisions des deux agents. Dans le cas particulier de la rémunération des directeurs d’entreprises, les données empiriques montrent qu’inclure des critères RSE dans la rémunération est plus adapté aux entreprises avec une forte interdépendance décisionnelle. La conclusion retrace le lien qui unit gouvernance et RSE à plusieurs niveaux, et discute de l’implication des réseaux et effets de mimétisme entre entreprise.
Keywords: Board of directors; CSR; Chefs d'entreprise; Conseil d'administration; Corporate Social Responsibility; Executive compensation; Gestion d'entreprise; Gouvernance; Gouvernement d'entreprise; Governance; RSE; Responsabilité Sociétale des Entreprises; Rémunération des dirigeants; Salaires; Strategic management; Stratégie d'entreprise

La rentabilité de l'investissement dans la responsabilité sociale d'entreprise "RSE" : pourquoi et comment ? - Espinassouze, Aline-Laure (CY Cergy Paris Université, 2018)
Selon le modèle théorique de la « RSE stratégique », la responsabilité sociale des entreprises, définie comme un investissement dans la qualité des relations avec les parties-prenantes stratégiques de l’entreprise, s’intègre dans la logique économique de l’entreprise. Partant de l’hypothèse d’une corrélation universellement positive entre RSE et FI, la question se pose du processus et du contexte par lesquels cette création de valeur s’effectue : si la RSE est un investissement rentable, peut-on expliquer pourquoi et comment ?La base de données Gaïa-Index mise à disposition par l’agence de notation RSE française EthiFinance permet d’étudier cette question sur une population d’entreprises françaises cotées de taille moyenne (N=230) durant la période 2011-2013. Les résultats sont en cohérence avec le consensus théorique et empirique sur la RSE stratégique et montrent que le « facteur humain » est un élément fondamental du processus de création de valeur permettant d’associer performance RSE et performance financière.
Keywords: CSR; Capital humain; Employee turnover; Human capital; Investissements; Investments; Performance; RSE; Strategy; Stratégie; Turnover

Cadres théoriques d’inspiration de recherches en contrôle de gestion et pilotage de la performance organisationnelle à l’ère de la responsabilité sociétale des entreprises (RSE) - Oubba, Omar; Akrich, Said (International Review of Economics, Management and Law Research, 2018)
L’objectif du présent article est d’essayer, à travers une étude théorique, de mettre en évidence les principaux cadres théoriques d’inspiration des recherches en contrôle de gestion et  le pilotage de la performance organisationnelle à l’ère du contexte actuel, caractérisé par une grande tendance des entreprises vers l’adoption et l’intégration de la RSE. Il ressort de la littérature une diversité d’approches et des courants de contrôle de la RSE.  Ainsi, les résultats escomptés stipulent qu’un grand nombre de recherches en contrôle de gestion et le pilotage de la performance organisationnelle à l’ère de la RSE, se réfère à la théorie des parties prenantes, la théorie de contingence, le cadre théorique de Simons (1990, 1991, 1994, 1995) et la théorie néo-institutionnelle. Ces théories constituent la référence fondamentale pour comprendre les déterminants du dynamisme, les évolutions voire les reconfigurations des systèmes de contrôle de gestion. Selon la littérature, les apports de la théorie des parties prenantes et ceux de la contingence permettent d’expliquer les tendances des entreprises vers la prise en compte des dimensions autres que financières et économiques de la performance. Aussi, la théorie de contingence fournit à l’entreprise une diversité des facteurs sur la base desquels elle peut concevoir les dimensions de sa performance organisationnelle élargie. Ainsi, le cadre théorique de Simons est une référence fondamentale pour comprendre la relation entre les stratégies des entreprises, leurs modes de pilotage et de contrôle, et les dimensions visées de la performance organisationnelle.
Keywords: CSR; Cadre théorique de Simons; Contingency theory; Contrôle de gestion; Management control; Neo-institutional theory; Performance; Pilotage; Piloting; RSE; Simons theoretical framework; Théorie de contingence; Théorie néo-institutionnelle

La Responsabilité Sociale des Entreprises : dynamique normative et enjeux concurrentiels. Une illustration d'un droit en mouvement - Thibout, Orianne (Université Côte d'Azur, 2018)
Concept désormais incontournable pour les entreprises dans la gestion, souvent corrélative, des risques juridiques et du risque de réputation afférents à leurs activités économiques, ainsi que dans la définition de leurs stratégies commerciales et concurrentielles, la Responsabilité Sociale des Entreprises (RSE) participe activement de l’abolition des frontières, d’ores et déjà poreuses, entre normativité d’origine publique et normativité d’origine privée. Dans un contexte concurrentiel mondialisé, elle met, dès lors, l’accent sur la nécessaire adaptation des instruments juridiques classiques à l’évolution d’une configuration normative complexe et ce, à l’échelle globale. Se faisant, la RSE fait l’objet d’un dialogue compétitif sans cesse renouvelé, entre pouvoirs publics nationaux et internationaux d’une part et pouvoirs privés économiques d’autre part. En ce sens, le droit économique contemporain, par capillarité normative et transfrontalière, n’est donc pas figé dans la durée, pas plus qu’il n’est cadenassé dans l’espace des frontières nationales.
Keywords: CSR; Competencia; Concurrence; Corporate Social Responsibility; Droit dur; Droit souple; Droit économique; Hard law; RSE; Responsabilité sociale des entreprises; Responsabilité sociétale; Soft law

La responsabilité sociétale des entreprises au Maroc : entre l’engagement effectif et l’investissement marketing - Mounir, Yaser; Moflih, Youssef (International Journal of Innovation and Scientific Research, 2018)
Le concept de responsabilité sociétale des entreprises (RSE) a une histoire longue et variée associée à l'évolution du concept et à la définition de la responsabilité sociétale des entreprises (RSE). Par ailleurs, bien qu'il soit possible de voir les empreintes de la RSE dans le monde, les écrits formels ont été les plus évidents aux États-Unis, où un nombre considérable de publications s'est accumulé. Ce mouvement de la responsabilité sociétale des entreprises a connu naissance dès les années 1950 aux Etats-Unis avant qu’il ne soit apparu en Europe lors des années 1990. En effet à partir de l’apparition de de l’ouvrage « Social Responsibilities of the Businessman (SRB) » de Howard R. Bowen qui est identifié comme le père fondateur de la notion de Responsabilité Sociale de l’entreprise, différentes définitions ont été rédigées par rapport à ce concept, et à ce jour aucune définition ne semble avoir le consentement dans le monde entier pour aboutir à une pensée universelle. Notre objectif à travers ce document est de mettre en évidence l'évolution conceptuel de la responsabilité sociétale des entreprises et nous présentons également les différentes définitions les plus largement utilisées qui sont de caractère exhaustif. The concept of corporate social responsibility (CSR) has a long and varied history associated with the evolution of the concept and the definition of corporate social responsibility (CSR). on the other hand, although it is possible to see CSR fingerprints around the world, formal writings have been most evident in the united states, where a considerable number of publications have accumulated. this movement of corporate social responsibility began in the 1950s in the United States before it appeared in Europe in the 1990s. indeed, from the appearance of the book «Social Responsibilities of the Businessman (SRB) » of Howard R. Bowen who is identified as the founding father of the concept of corporate social responsibility, different definitions have been written in relation to this concept, and to this day no definition seems to have the consent around the world to achieve universal thinking. our objective through this document is to highlight the conceptual evolution of corporate social responsibility and we also present the various most widely used definitions that are exhaustive in nature.
Keywords: Business; CSR; Corporate Social Responsibility; Entreprise; RSE; Responsabilité sociale/sociétale; Society; Société

Assessing the nexus between corporate governance, corporate social responsibility and corporate regulation: the way forward for the OHADA zone - Tambutoh, Dashaco John; Tarh, Bande Gulbert Mbah (International Journal of Advanced Research and Publications, 2018)
Encyclopaedic Corporate Governance (CG) is now a mainstream issue of concern in the business world. Yet, there has been no systematic investigation of CG practices in general, allowing for a distinction between the profit and non-profit organizations. In this regard, this article aims to investigate the nuances in the application of sound governance principles across different types of organizations in general, together with the understanding and applications of Corporate Social Responsibility (CSR) and Corporate Regulation (CR) in the context of the OHADA zone. With CSR envisages as a model of CG that extends the fiduciary duties from fulfilment of responsibilities towards the shareholders of the firm to fulfilment of analogous fiduciary duties towards all the firm?s stakeholders. Thus, after considering the place of CSR in the debate about alternative CG modes, a full-fledged social contract foundation of the multi-stakeholder and multi-fiduciary model is present. The article, therefore, shows that CSR is a social norm that would endogenously emerge from the stakeholders? social contract seen as the first move in an equilibrium selection process that reaches the equilibrium state of a CG institution; and as a global trend involving corporations, states, international organizations and civil society organizations. Besides, the article portrays the trend of CSR in three ways: as a regulatory framework that places new demands on corporations; as a mobilization of corporate actors to assist the development aid of states and; as a management trend. With each of these portraits suggesting certain actors, relations, driving forces and interests as being central. These multiple identities may partially describe the trend?s success, but could equally well describe its contestation, fragility and fluidity. Based on the argument that CSR is not just a fashion but rather the future from another angle, the article explicitly explores the nexus between CSR, CG and CR as appreciated in the OHADA zone. It also presents fresh insights into the applications of CG and CSR principles under the OHADA perspective that has not received systematic attention and consideration in the literature and, thus, provides policy recommendations to mainstream a viable CSR framework in the OHADA zone.
Keywords: Corporate Regulation; Corporate Social Responsibility; Corporate governance; OHADA

La responsabilité des entreprises en matière de droits de l'Homme - Soudain, Tennessee (Université de Strasbourg, 2018)
La responsabilité des entreprises en matière de droits de l'Homme (REDH) a émergé face à la quasi-impunité des violations commises par les entreprises. Cette responsabilité est nouvelle au sein des différents ordres juridiques en raison de la difficulté d'adapter les techniques traditionnelles du droit à la globalisation des relations économiques. Le paradoxe de la REDH tient à ce qu'elle ne devrait pas impliquer la création de nouvelles obligations car les États disposent déjà des outils nécessaires au respect des droits par les entreprises sous leur juridiction. Dans une économie mondialisée, les questions liées à la responsabilité des entreprises doivent nécessairement être envisagées de manière globale pour être réglées efficacement. En effet, la complexification des structures des entreprises, l'internationalisation de celles-ci et le développement des chaînes d’approvisionnement marqué par un nombre croissant de sous-traitants aboutissent à des rattachements juridiques multiples. The human rights corporate responsibility (HRCR) has emerged due to the near-impunity for corporate abuses. This responsibility is new within the different legal systems as it is difficult to adapt traditional legal techniques to the globalization of economic relations. The paradox of human rights corporate responsibility is that it should not imply the creation of new obligations since States already have the necessary tools to ensure that human rights are respected by companies under their jurisdiction. In a globalized economy, corporate responsibility issues must necessarily be considered in a global perspective to be effectively addressed. Indeed, the increasing complexity of groups' structures, their internationalization and the development of supply chains caracterized by an increasing number of subcontractors lead to connections with more than one legal order.
Keywords: CSR; Corporate; Droits de l'Homme; Droits de l'Homme (droit international); Entreprises; Entreprises multinationales; Human rights; RSE; Responsabilité sociétale des entreprises multinationales

Vers une meilleure compréhension des déterminants spécifiques à la croissance des PME opérant en Afrique : cas du Bénin - Aïhounhin, Sègbédji Parfait (Université Laval, 2018)
L’objectif global de cette thèse est de montrer, que la spécifié des déterminants de croissance d’entreprise est fonction des environnements d’affaires. L’Afrique étant plurielle et multiple de par sa culture, ses moeurs, ses environnements d’affaires, nous avons opté d’étudier le Bénin. Pour atteindre cet objectif global, un sous-objectif est retenu par article parmi les trois que comporte cette thèse. Dans le premier article, il s’est agi de faire une synthèse globale des déterminants de la croissance des PME en les catégorisant. Dans le deuxième article, nous avons procédé à la confirmation des déterminants pertinents (spécifiques) pour le contexte étudié. Dans le troisième article, nous avons évalué l’effet des déterminants retenus sur la croissance des PME étudiées. Ainsi, une approche par étape est utilisée pour atteindre les objectifs précités. Lors de la première étape, une revue systématique de la littérature a permis de faire le point des déterminants de la croissance des PME ainsi qu’une mise en exergue d’un certain nombre de facteurs émergents à étudier (1er niveau de résultat). À la suite de cette étape, nous avons, sur la base d’une analyse en composante principale, essayé de retenir parmi les facteurs émergents, ceux qui pourraient être qualifiés de déterminants spécifiques (2e niveau de résultat). En dernier lieu, à l’aide de la régression panel, nous avons étudié les effets des déterminants spécifiques retenus sur la croissance des PME de notre échantillon (3e niveau de résultat). Entre autres résultats, cette étude met l’accent sur l’importance de certains déterminants spécifiques à la croissance des PME, tels les recours aux compétences externes, les investissements en recherches et en développement et la responsabilité sociale des entreprises.
Keywords: Innovation; PME; Petites et moyennes entreprises; Responsabilité Sociale de l'Entreprise

El contenido del acuerdo social de ejercicio de la acción social de reponsabilidad. Especial referencia al ámbito subjetivo - Moreno Buendía, Francisco Jesús (Estudios sobre la responsabilidad de los administradores de las sociedades de capital a la luz de sus recientes reformas legislativas y pronunciamientos judiciales, 2018)

The directors’ fiduciary duty to act in the best interests of the company: the possible developments of common law by statute and how they affect human rights - Nomadwayi, Bakhulule (University of KwaZulu-Natal, 2018)
This research traces the developments of the directors’ fiduciary duty to act in the best interests of the company and looks at how these developments affect human rights and interests of stakeholders. The main focus of the study is on the human rights impact of this duty. Initially, this duty was only regulated in terms of common law which proved to be problematic. The problem with common law lies within the definition of ‘best interests of the company’, which not only exclude the interests of other stakeholders but also has the potential to bring about violation of human rights, particularly the rights to equality, dignity and fair labour practice. At common law best interests of the company means interests of the company itself and its shareholders. The common law only protects the company and its shareholders, while excluding the rights and interests of stakeholders. The common law duty to in the best interests of the company is not in line with our contemporary law because it ignores human rights. The neglect of human rights by this duty renders it inconsistent with the values contained in the Constitution. Furthermore, the exclusion of stakeholders’ rights by this duty cannot be justified because stakeholders play an important part in safeguarding the stability and continued existence of the companies. The fiduciary duty to act in company’s best interests is now contained in the Companies Act of 2008. Inclusion of this duty in the Act enables our courts to interpret it in a manner that protects human rights and which takes into account interests of other stakeholders. Section 7 (a) of the Act provides that among other goals of the Act is the promotion of compliance with the Bill of Rights when applying the company law. The impact of section 7 is that it imposes an indirect duty on directors to consider the human rights impact of their decisions. Section 158 of the Act enables the courts to “develop common law as it is necessary to improve the realisation and enjoyment of rights established by the Companies Act of 2008.” Given this recognition of the Bill of Rights by the Companies Act, it’s of vital importance that our courts should interpret and apply the duty to act in the best interests of the company in manner that is consistent with the Constitution. Directors are now obliged to pay attention to the human rights impact of their decisions.
Keywords: Best interests of the company; CSR; Corporate Social Responsibility; Fiduciary duty

L'évolution du business model de l'entreprise sociale, le cas des entreprises des TIC : une étude comparative de cas France/Sénégal - Ndour, Mamour (Sorbonne Paris Cité ; Université Gaston Berger, 2017)
Cette thèse s'intéresse au concept d'entrepreneuriat social qui combine un projet économique et une finalité sociale. Durant les premières étapes de développement du projet, les startups sociales sont souvent confrontées à une évolution de leur business model (BM) pour faire face aux contraintes organisationnelles mais également aux menaces et aux opportunités de leur environnement. Notre objectif dans cette recherche est d'identifier les mécanismes qui permettent de concilier l'« économique » et le « social » à travers la problématique suivante : comment garder l'équilibre entre la dimension économique et la dimension sociale du BM de l'entreprise sociale face à son environnement ? Ainsi, nous avons mobilisé une approche mixte (contenu et processus) pour étudier l'évolution du BM des startups sociales. Cela nous a permis de répondre aux questions subsidiaires du « pourquoi » et « comment » ainsi du « quoi » de l'évolution du BM des entreprises sociales. Pour répondre à cette problématique, nous adoptons une approche qualitative par une étude comparative de startups sociales des TIC (technologies de l'information et de la communication) en France et au Sénégal. Les données collectées par entretiens semi-directifs (55 au total) et lors d'évènements (meet-up, conférences, panels, salons, etc.) sont enrichies de données secondaires (sites web, documents internes, rapports, etc.). Ce corpus de données a fait l'objet d'un traitement avec le logiciel Nvivo 11. Les résultats de ce travail de recherche peuvent être déclinés comme suit : D'abord, notre recherche enrichit la littérature de nouveaux facteurs externes et internes qui influencent l'évolution du business model à savoir la levée de fonds, les subventions, l'augmentation de l'impact social et l'autonomie financière. Ensuite, nous avons identifié les éléments du BM qui évoluent avec les phases de développement des startups de même que leurs logiques d'évolution. Puis, notre principale contribution consiste en l'identification des principaux mécanismes qui peuvent permettre de garder un bon équilibre entre la dimension économique et la dimension sociale du BM lorsque ce dernier évolue. Enfin, nos résultats montrent les différences et les similitudes de l'évolution des BM des cas en France et au Sénégal en analysant leur écosystème entrepreneurial. This thesis focuses on the concept of social entrepreneurship, which combines an economic project and a social purpose. During the early stages of project development, social startups often face challenges in their business model (BM) due to organizational constraints, but also threats and opportunities of their environment. Our goal in this research is to identify the mechanisms that allow to reconcile the 'economic' and 'social' through the following issue: How to keep balance between the economic and the social dimension of social enterprise's BM in the face of its environment? Thus, we have mobilized a mixed approach (content and process) to study the evolution of the BM of social startups. This has allowed us to meet the ancillary issues of the 'why' and 'how' as well as the ''what'' of the evolution of the BM of social enterprises. To answer our research question, we have adopted a qualitative approach by conducting a comparative study of social startups of ICT (information and communication technologies) in France and Senegal. Fifty five (55) in-depth interviews supplemented with secondary data (websites, internal documents, reports, etc.) was analyzed thanks to the assistance of the software Nvivo 11. As regards our results : first, our research enriches the literature of new internal and external factors that influence the evolution of the BM like fundraising, grants, the increase of the social impact and financial independence. Second, we have identified the elements of the BM that change with the startups development phases, as well as their logical evolution. On the other hand, our main contribution remains on the identification of main mechanisms that can allow to keep a good balance between the economic dimension and the social dimension of the BM when the latter evolves. Finally, our results show the differences and similarities in the evolution of the BM between the Senegal and France thanks to their entrepreneurial ecosystem.
Keywords: Business model; Development; Digital; Entrepreneuriat social; France; Numérique; Responsabilité sociétale; Senegal; Social entrepreneurship; Start-up; Startup; Sénégal; Évolution

Les piliers social et culturel du développement durable en droit - Tshitende Wa Mpinda, Guillaume (Université de Limoges, 2017)
L’analyse des piliers social et culturel du développement durable en droit évoquée dans ce travail est une contribution à l’étude du développement durable. La finalité poursuivie est la promotion, l’intégration et l’efficacité du développement durable dans les politiques publiques. On observe que l’économie et l’environnement peuvent se prévaloir de ces trois éléments. La reconnaissance du développement durable par le social et le culturel a connu certains ralentissements scientifiques et politiques. Or, le social et le culturel on fait leur preuve depuis le PIDESC. Nombreux textes régionaux reconnaissent la nature juridique et l’impact du social comme de la culture dans l’économie etl’environnement. Le PIDESC est la preuve d’unité des sources entre économie, social et culturel. Il a contribué au rattachement (volontaire ou involontaire) entre ses différents éléments. Malheureusement, les conséquences de ce rattachement a conduit soit à l’illisibilité du social soit à l’oubli total du culturel dans les politiques publiques nationales, régionales et internationales. Les questions sociales et culturelles revalorisent le développement durable et l’intègre dans nos sociétés par son acceptation par l’ensemble d’acteurs internationaux, régionaux et nationaux qui ont un rôle majeur à jouer pour la faisabilité du développement durable dans nos territoires. C’est dans cette condition d’accord permanent que le développement durable se focalise sur le respect des droits fondamentaux en mettant en valeur certains dispositifs indispensable à sont respect dans notre société. Il s’agira de l’éthique, de l’équité sociale, de la justice sociale et d’autres instruments comme la RSE des codes de bonnes conduites et l’ISR. Il tient au même moment compte de la diversité culturelle. Sauf que la majorité de ces éléments reposent sur le Soft Law. Il s’en suite que, de plus en plus, on assiste à un rapprochement réel entre culture et développement durable. En définitive, il appartient au juge de donner tout le sens au développement durable et d’équilibrer le rapport de force entre ces différentes composantes. Cette mission est d’autant importante qu’il s’en dégage le fait que le développement durable peut être considéré non plus comme un principe mais plus tôt comme un droit.
Keywords: Droit; Développement durable; Environnement; Sustainable development

Modélisation d’un Indice de Performance de la Responsabilité Sociétale selon la norme ISO 26000 - Fethallah, Widad; Chraibi, Lotfi; Sefiani, Naoufal (International Journal of Innovation and Scientific Research, 2017)
Le présent travail consiste à développer un nouveau modèle relatif à l’évaluation de la performance responsabilité sociétale de l’organisation (RSO) basé sur une approche holistique et interdépendante issue des fondements et principes de la norme ISO 26000. Le modèle d’évaluation proposé génère des indices de mesure RSO, qui aideraient l’organisation à caractériser et évaluer sa performance par rapport aux sept questions centrales, dans le but d’améliorer sa démarche RSO, et ce dans une logique participative avec ses diverses parties prenantes. Inspiré des travaux de G. K. Kanji et P. K. Chopra, nous proposons un modèle d’équations structurelles composé de variables latentes et de variables manifestes. L’avantage du modèle permet de mieux cerner les diverses connections et causalités entre les différentes composantes (les questions centrales). L’implémentation du modèle sur le logiciel XLSTAT fournit des indices de mesure pour chaque variable latente qui peuvent être analysés et interprétés afin de développer les plans d’actions et les aspects à améliorer dans la démarche RSO. The aim of the present work is to develop a new model to assess the Corporate Social Responsibility CSR performance of an organization based on a holistic and interdependent approach as described in the foundations and principles of the ISO 26000 standard. The proposed model generates a new Corporate Social Responsibility (CSR) Index, which help the organization to characterize and assess its performance regarding to the seven core subjects of ISO 26000 standard, with the different stakeholders. Inspired by the work of G. K. Kanji and P. K. Chopra, we propose a model of structural equations composed of latent and manifest variables. The model identifies the various connections between the different components (the core subjects). The implementation on the XLSTAT software provides an index for each latent variable that can be analysed in order to improve the CSR performance.
Keywords: CSR Index; Corporate Social Responsibility; Indice RSO; Latent Variable; Manifest Variable; Modèle d’équations structurel; Partie prenante; Responsabilité sociétale de l’organisation; Stakeholders; Structural Equation Model; Variable Manifeste; Variable latente; XLSTAT Software; logiciel XLSTAT

Trade, labour and sustainable development: an integrated perspective - Khan, Zobaida (McGill University, 2017)
Some contemporary challenges for global trade regulation and labour governance arise from the barriers between questions of law and social justice, and development policy and distributional issues. This thesis attempts to address some of these regulatory or governance challenges by exploring the interactions between sustainable development (SD), trade regulation, and social or distributive justice. Borrowing from multiple disciplines, i.e. law, international relations, and development economy, and focusing on the problems of low-income countries, this thesis examines the potential and importance of a broad ideational objective in introducing transformative changes in different regulatory or governance mechanisms. This thesis does not discuss ways to link trade regulation or labour governance with SD; rather here the possibilities of operationalizing SD, within the global trade regulatory site or transnational governance mechanisms, are explored from a capability perspective. It is argued that a capability-based understanding can resituate some questions on trade-SD interaction and introduce important behavioural changes in the functioning of the World Trade Organization (WTO). Yet, ongoing operationalization of capability-based SD requires effective market complementary interventions from governance mechanisms operating at different spaces and with diverse actors. Certain emerging transnational governance mechanisms, which connect broader social or distributional issues such as labour governance with trade opening or economic cooperation, attempt to provide crucial market complementary interventions. Taking examples from the recent transnational safety initiatives for Bangladeshi garment workers and relying on a broad conceptualization of the social or distributional issues, it is argued that attention to capability enhancement produces a much more compelling form of labour governance mechanism at these hybrid sites. With a focus on capability-based SD, a model of transformative linkage is proposed for effective labour governance. The model demands that fundamental and redistributive rights of labour are interconnected and appropriate labour governance requires a stronger form of corporate responsibility. Analyzing the interaction of diverse rules, governance processes and mechanisms, with the demands of marginalized forces the global hegemony of capital is juxtaposed with available options and possible alternatives.
Keywords: Corporate Social Responsibility; Labour; Social justice; Sustainable development; Trade regulation

A responsabilidade social corporativa face aos danos ambientais sob a perspectiva do direito internacional - Nunes, Bárbara Nogueira (Universidade Federal Fluminense, 2017)
A governança global é um fenômeno relativamente novo na ordem internacional. A responsabilidade social corporativa surge como um mecanismo da governança global no que tange à responsabilização das sociedades que assumem atribuição cada vez mais relevante diante do mundo globalizado. Os danos ambientais comumente são fruto da ausência de instrumentos efetivos de responsabilidade. O descarte de resíduos sólidos nos oceanos há tempos vem acontecendo e prejudica o meio ambiente marinho vinculado às águas brasileiras. A comunidade internacional enfrenta o descarte de resíduos em águas internacionais basicamente por meio da elaboração de uma legislação que objetiva regulamentar o despejo de resíduos nos oceanos. Assim, cabe investigar se há uma efetiva resposta ao enfrentamento do problema em termos da logística jurídica atualmente utilizada e sua fiscalização pela comunidade internacional. Parte-se da hipótese de que os instrumentos legais em vigor não se apresentam como uma solução estanque ao problema ante a argumentação da soberania dos Estados que leva a não observância das normas internacionais e a não responsabilização dos infratores. Um mecanismo mais eficaz em termos de regulamentação e de fiscalização, aliado à conscientização e educação ambiental são exigências que se fazem necessárias para combater os efeitos dessa prática que ecoa um dano permanente ao meio ambiente marinho. A metodologia utilizada neste trabalho dar-se-á através da análise teórica sobre o fenômeno a partir de doutrina selecionada que trata das construções conceituais que abordam o tema.
Keywords: Challenges; Comunidade internacional; Corporate Social Responsibility; Dano ambiental; Desafios; Descarte de resíduos; Gerenciamento de resíduo; Global governance; Governança global; Internation; Ocean dumping; Poluição ambiental por resíduo industrial; Responsabilidade social corporativa; Responsabilidade social da empresa; Solid environmental damage; Sólidos danos ambientais; Waste disposal

The international legal framework on business and human rights and its domestic operationalisation : strategic litigation on mining and a healthy environment in South-Africa - Verdonck, Lieselot (Ghent University, 2017)
The debate on business and human rights attracts the interest of many parties, and regularly makes the headlines. On 19 January 2017 De Morgen, for instance, ran the following headline: “These banks do business with companies that violate human rights and nature”. The discourse suggests that few question that business enterprises should respect human rights. The legal meaning and consequences of associating 'business' with 'human rights' remain contentious, however. By clarifying the existing legal framework this thesis seeks to rationalize the debate. Special attention is paid to enforcing the responsibility of business enterprises for human rights through domestic judicial remedies. The analysis is concretised through a case study on adverse human rights impacts of environmental degradation caused by mining in South Africa. Based on the findings of the study, the thesis reflects on how the international legal framework on business and human rights should be developed further.
Keywords: Business; CSR; CSR disclosure; Human rights; International law; RSE; South Africa

L'action en justice des parties prenantes dans le cadre de la Responsabilité Sociale de l'Entreprise - Lopez, Laëtitia (Université Jean Moulin Lyon 3, 2016)
L’action en justice intentée en matière de Responsabilité Sociale de l’Entreprise révèle certaines limites lorsque les justiciables parties prenantes souhaitent protéger leurs intérêts. Par une juridicisation du droit de la RSE à mi-chemin entre la soft law et la hard law, l’action en justice des parties prenantes pourrait être véritablement efficiente. Dès lors, les mécanismes processuels traditionnels sont insuffisants lorsqu’il s’agit d’agir en justice dans ce domaine. C’est notamment à travers l’intérêt et la qualité à agir en justice des parties prenantes que des aménagements de la procédure civile vont être véritablement nécessaires. Des améliorations supplémentaires telles que l’instauration d’une action de groupe élargie au domaine de la RSE et davantage américanisée permettrait notamment aux parties prenantes d’assurer leur défense grâce à un dispositif nouveau très efficace. De plus et par la voie extrajudiciaire des modes alternatifs de règlement des litiges, les acteurs de la RSE peuvent également décider de porter le différend qui les oppose hors de la connaissance du juge étatique. Ce choix d’action peut être révélateur d’une préférence pour une justice davantage négociée. Ces propositions semblent être indispensables à la mise en œuvre d’une action en justice efficace en matière de RSE. Les parties prenantes pourront alors agir en justice de manière inédite afin de parachever leur protection. Les nécessités juridiques et sociales actuelles semblent ainsi faire évoluer le droit afin que les parties prenantes puissent bénéficier d’une action en justice considérée comme un véritable contre-pouvoir face à l’entreprise.
Keywords: Action de groupe; Action en justice; Actions et défenses; Alternatives methods of settlement of disputes; CSR; CSR law's judicialization; Civil Procedure; Collective action; Conditions d'existence de l'action en justice; Corporate Social Responsibility; Droit d'agir; Intérêt à agir en justice; Juridicisation du droit de la RSE; Legal action; Legal action's conditions; Legal competency/active legitimation; Legal interest; Legal standing; M.A.R.L.; Modes alternatifs de règlement des litiges; Normes volontaires; Parties prenantes; Procédure civile; Qualité à agir en justice; RSE; Responsabilité Sociale de l'Entreprise; Responsabilité sociétale; Stakeholders; Vonluntary standards

CSR and financial performance parameters of DBBL: An empirical analysis - Farijul, Islam; Rahman, Mostafizur (International Journal of Innovation and Scientific Research, 2016)
The purpose of the current study is to show the statistical linkage between CSR expenditure of financial service firm mainly DBBL and its financial performance on the basis of some key parameters that attempts to contribute to the existing knowledge of corporate social responsibility initiatives by businesses and its ability to influence their financial performance. Consequently, the main objective is to examine the relationship between CSR and financial performance of the banking sector. For this purpose, various financial drivers are used such as EPS, DPS, NPAT, ROE, EVA ROA, MVA and, ROE and ROI. After getting all the relevant data from secondary sources like annual reports and reports from Bangladesh Bank, statistical tool like multivariate analysis in the form of Bi-variate Regression is used to depict the relationship and the developed hypotheses are tested by using Univariate analysis in the form of one sample t test under parametric test. The major finding of this study demonstrates evidence that there is a statistical significant linkage between CSR and Performance of the sample bank.
Keywords: CSR; DBBL; Financial performance parameters

Accountability of multinational corporations for human rights violations under international law - Mnyongani, Freddy (University of South Africa, 2016)
Jurisprudence
Keywords: CSR; Corporate Social Responsibility; Corporate governance; Human rights; International business enterprises; Liability for human rights violations; RSE; Social responsibility of business; Tort liability of corporations

Institutionella samspel : Om möten mellan en kommersiell och en ideell logik - Kvarnstrom, Emilia (Företagsekonomiska institutionen, Uppsala universitet, 2016)
Institutional logics create order and stability. They organize interaction and prescribe how we should behave towards each other. Such logics have generally been regarded as exclusive, in the sense that an organizational field is always guided by a single institutional logic. If there are two or more institutional logics in one setting at the same time this will create conflicting demands and contradictions. So how do organizations and individuals that act in these settings, where different institutional logics do meet, cope with the conflicting demands? This question is researched by studying actors who organize partnerships between corporations and non-profit organizations. Institutional logics have typically been studied at field level. My study follows a more recent literature strand focusing on individuals and their way of coping with conflicting institutional logics. In this thesis, interviews, text analysis and observations are used. The interviews were conducted with CSR managers of corporations, managers of corporate partners at non-profit organizations, CSR consultants, and project managers of intermediary organizations. These actors are working in an environment where conflicting institutional logics are played out. Using a narrative approach it is shown how these actors are aware of their institutional environment and its conflicts which requires them to constantly act as translators. The study shows that the actors organize an interplay between a market-logic and a social-welfare logic by bringing together the logics and establishing limits to what extent logics can be mixed. Thus, the actors can be understood as bilingual, rather than hybrids. Furthermore, it is argued that a narrative approach provides the possibility to understand institutional logics in empirical contexts as more present and visible than they are usually considered to be. The study concludes that bilingual actors balance conflicting demands and negotiate requirements set by institutional logics in their day-to-day work. Settings where institutional logics meet can hence be understood as both a contradiction and an ongoing interplay.
Keywords: Actor; Cross-sectoral partnerships; Hybrid organization; Institutional logics; Institutional theory; Narrative; Partnerships

Social legitimacy in the internal market : a dialogue of mutual responsiveness - Mulder, Jotte (European University Institute, 2016)
Social legitimacy is conventionally conceived to encompass an empirical notion based on the idea that, lacking societal acceptance, a (political or legal) regime will eventually disintegrate. This concern is reflected in the original compromise of 'embedded liberalism', which stands at the basis of the internal market of the European Union. The primary law set up of the internal market, indeed, shares the idea that the benefits of a joint commitment to free trade can only be achieved in a sustainable way if combined with an acknowledgement of domestic societal objectives within the same frameworks. Nevertheless, social legitimacy will eventually depend on the institutional design and structural rationales that embed societal values within such regimes and vice versa. This perspective is further developed, normatively, on the basis of the work of Karl Polanyi and adopted to critically assess the structural rationales that are developed within internal market adjudication, which the thesis approaches as a separate field of social ordering within the European Union. Thus, social legitimacy is developed as a requirement that perceives the legitimacy of internal market law on the basis of the extent to which it can respond and integrate social practice and values. On this point the thesis finds that the internal market lacks a sufficiently developed rationale or "common language" that is able to address the normative concerns of social legitimacy. Societal realities are often valued within a metric that risks doing violence to potentially genuine and worthwhile aspects of Member States' 'social spheres'. The thesis develops that the normative claims of social legitimacy are best addressed on the basis of a rationale of mutual responsiveness, which is considered a necessary but underdeveloped element of the constitutional form and social purpose of the internal market that is implicit in the constitutional theory of transnational effects. From a perspective of mutual responsiveness, the social purpose of the internal market is not to condition choices that necessarily require the market to trump the social sphere - or the opposite- to allow the social to necessarily trump the market. Mutual responsiveness advances a more holistic approach that conceives the market and the social, literally, as 'communicating vessels'. The normative concerns of social legitimacy and the potential of mutual responsiveness to address these normative claims are the central and connecting elements throughout the thesis.
Keywords: Commercial law; European Union countries; Free Trade; Trade regulation

Corporate Social Responsibility , Oil Exploration and the Niger Delta Question - Obi, Emeka Anthony (Oman Chapter of Arabian Journal of Business and Management Review, 2015)
The intricate relationship between corporate organizations and their environment is one that is supposed to be based on mutual interdependence. This is because the organization depends on the environment for its inputs, while the environment also needs the organization for its sustenance. This therefore calls for a symbiotic relationship between them. It is this realization that gave birth to the concept of Corporate Social Responsibility (CSR). This paper tries to look at the application of the concept as it concerns the oil companies operating in the Niger Delta region of Nigeria within the ambit of the Niger Delta question. The study employs the systems theory as an analytical framework. It tries to situate the concept of CSR within the general neglect by successive governments of this region that sustains the entire Nigerian state. The implication of the above is that a better understanding of the problem of CSR in the Niger Delta region becomes easier when juxtaposed with the attitude of the Nigerian state towards the region over the years. It is the summation of the paper that the oil companies have not been very proactive in this regard and as such have been perceived by their host communities as enemies and exploiters instead of partners. The study concludes by insisting that while the oil companies should be more proactive, the government on her part should step up the tempo in ameliorating the deplorable condition of the golden goose.
Keywords: CSR; Corporate Social Responsibility; RSE; Responsabilité Sociale de l'Entreprise

Labour rights and working conditions in corporate codes of conduct: an assessment of the legal dimension, in different national contexts, of selected multinational corporations’ corporate social responsibility commitments - Tiemeni, Thierry Galani (University of the Western Cape, 2015)
At the heart of this thesis is the notion of Corporate Social Responsibility (CSR), an innovative concept deep-rooted in the globalisation phenomenon. The notion of CSR entails the much-debated duty of businesses, not only to comply with international and local standards in terms of, inter alia, labour rights and working conditions, human rights and environmental protection, but also to be at the forefront of voluntary and uplifting actions geared toward addressing societal issues and concerns. For corporations, it is about moving from the traditional approach of business as an activity with the sole purpose of realising profit towards acknowledging the need to integrate societal and environmental issues and concerns into their business purposes. The thesis examines selected multinational corporations’ (MNC) approaches to CSR as contained in their codes of conduct, in an effort to reach a comprehensive understanding of the purpose, interest and practices of businesses engaging in CSR activities. Particular attention is given to the analysis of labour orientated measures implemented by selected MNCs as they undertake to voluntarily act as proponents of the theory of the necessity of socially responsible businesses. The aim is to comparatively assess the legal dimension and the relevance, in different countries, of these MNC CSR commitments. The first part of the thesis is theoretical and has the purpose to present a comprehensive analysis of CSR against the current legal framework, at a global scale and within the context of selected countries. The thesis will explore the notion of CSR in order to present its definition and characteristics, briefly retrace its history, differentiate it from related and/or similar concepts, and finally assess the extent of its introduction and adaptation into various national and international institutional frameworks. Even though initially addressing the issue of CSR in the current legal framework as a whole, the scope of the thesis will ultimately be reduced to focus only on labour-related aspects of CSR. The aim of the thesis is to assess MNC’s CSR commitments, and subsequently highlight the interaction between CSR, labour and employment legal frameworks (at national and international level) and the effective implementation of labour rights and working conditions as observed in the context of different countries. More importantly, the thesis will also include a comparative analysis of CSR principles included in selected MNC codes of conduct, in order to assess the extent of their compliance with national labour legislation, international labour standards, as well as the standards and principles set by national and international CSR instruments and institutions. The purpose of such an exercise is to thoroughly assess the impact of a national context - in terms of national legal, economic, social and industrial framework - on the legal dimension, and the relevance of MNCs CSR commitments. A crucial argument developed in the thesis refers to the fact that MNC codes of conduct may have the potential to impact on labour rights and working conditions of a MNC across the different countries into which the MNC operates. Finally, considering the fact that as a topic CSR is a potentially controversial subject, it is necessary to point out, from the onset, that the thesis engages with the subject from a critical perspective. The approach therefore entails critically analysing and discussing MNC commitments and practices as observed in different countries, so as to be able to ascertain and comprehend the impact of a national context on the content, the relevance and the legal dimension of MNC codes of conducts
Keywords: Code of conduct; Corporate Social Responsibility; Labour rights; Multinational corporations; Working conditions

Responsabilité sociale de l'entreprise (RSE), responsabilité éthiques et utopies, Les fondements normatifs de la RSE, Etude de la place du droit dans les organisations - Cadet, Isabelle (Le CNAM, 2014)
Cette thèse sur travaux porte sur la recherche des fondements normatifs possibles de la Responsabilité Sociale de l’Entreprise (RSE). C’est une analyse approfondie de la notion de norme, de ses fonctions en tant qu’outil de gestion, de ses limites en dehors de toute éthique. Le sujet est traité de manière transdisciplinaire : l’apport théorique des sciences de gestion s’appuie sur l’étude empirique du droit, comme révélateur des utopies, réalisables ou non, en matière de RSE. les responsabilités dites éthiques sont-elles une nouvelle idéologie, une espèce de rêve social qui ne se soucie guère des étapes réelles dans la construction d'une nouvelle société, ou un nouveau pouvoir de la connaissance, un projet d'organisation politique, fondée sur l'axiologie des droits de l'Homme? L’étude de la place du droit au sein de la RSE est un moyen de revisiter de nombreuses théories des organisations, notamment sur la gouvernance, les parties prenantes, la démocratie, le développement durable, le risque, la responsabilité. Elle conclut à la nécessité du respect préalable du droit dans la création et l'utilisation des outils de gestion. L'objet de la recherche, à la croisée des chemins entre les sciences de gestion et les sciences juridiques, autorise néanmoins une réflexion critique sur la flexibilité de la règle de droit et la régulation par les normes, devenues de plus en plus souples et floues, causes d’une privatisation du système économique global. Prenant la mesure des mutations normatives dans la gouvernance mondiale, cette thèse propose de surmonter le défi de l’internormativité, par une nouvelle éthique de la responsabilité. L’idée, en France, serait de concevoir la responsabilité sociale des entreprises comme la fiction juridique de l’entreprise citoyenne. Une véritable extension de responsabilité préventive serait à la charge des sociétés personnes morales dans le cadre de leur sphère d’influence.
Keywords: CSR; Corporate Social Responsibility; Droit flou; Droit souple; Ethics; Ethique; Fuzzy law; Gouvernance; Governance; ISO 26000; Norm; Normalisation; Normalization; Norme; Norme ISO 26000; Organisation; Organization; RSE; Regulation; Responsabilité sociale de l'entreprise; Responsabilité sociétale -- Normes; Risk; Risque; Régulation; Soft law; Tétranormalisation; Tétranormalization; Éthique des affaires

Analyse perceptuelle des déterminants de l'engagement sociétal des entreprises marocaines labellisées RSE : de la performance au développement durable - cas du maroc - Taoukif, Fatima Ez-Zahra (Université de Toulon, 2014)
L’objet de cette thèse est d’analyser les déterminants de l’engagement sociétal des entreprises labellisées RSE, dans un contexte de pays émergent, en l’occurrence le Maroc. Sachant que la démarche de RSE ne connaît pas le même succès dans le monde pour plusieurs raisons liées aux spécificités économiques, culturelles et sociales de chaque pays, ce travail de recherche propose d’analyser empiriquement les bénéfices et freins perçus par les entreprises labellisées RSE de la Confédération Générale des Entreprises Marocaines (CGEM). En effet, face à un contexte marqué par des mutations profondes du nouvel environnement économique international, à savoir, la mondialisation économique et la globalisation financière et les modifications réglementaires et technologiques importantes, il est devenu nécessaire pour l’entreprise de s’inscrire dans des orientations stratégiques portant sur les perspectives du développement durable, et mettant en lumière l’engagement sociétal dans les pratiques managériales dont l’objectif principal est d’assurer sa pérennité. C’est ainsi qu’elle peut concilier préservation de l’environnement et équité sociale d’un coté et les impératifs financiers et économiques de l’autre. En se basant sur des thématiques relatives aux variables démographiques, degré de connaissance et posture managériale, actions menées et outils mobilisés, freins et réticences, et motivations et avantages en matière de RSE, nous mettons l’accent sur les bénéfices et inconvénients de cette démarche.Pour cela, deux parties ont été consacrées pour élucider les différentes questions posées. Après avoir présenté un panorama des approches théoriques et conceptuelles de l’engagement sociétal des entreprises dans la première partie, la deuxième sera consacrée au positionnement épistémologique et méthodologique, et à l’analyse des résultats de l’étude empirique. Les dits résultats permettent de répondre à notre interrogation : Quels sont les déterminants de l’engagement sociétal des entreprises marocaines labellisées RSE?
Keywords: Advantages; Analyse du contenu thématique; Analyse perceptuelle; Analysis of the thematic contents; Analysis perceptuelle; Ascending Hierarchical classical; Avantages; CSR; Certified companies in Morocco; Classification Hiérarchique Ascendante; Community involvement; Company's social responsibility; Engagement sociétal; Entreprises labellisées au Maroc; Gestion d'entreprise; Maroc; Planification stratégique; RSE; Responsabilité Sociale de l'Entreprise; Responsabilité environnementale; Responsabilité sociétale; Éthique des affaires

Le droit à l'épreuve de la responsabilité sociétale des entreprises : étude à partir des entreprises transnationales - Caillet, Marie-Caroline (Université de Bordeaux, 2014)
Les entreprises sont aujourd’hui au coeur des échanges économiques mondiaux. Ces échanges se traduisent par la mise en place de relations commerciales desquelles peuvent émerger des structures souvent complexes et difficilement saisissables par le droit : les entreprises transnationales. Aucune réponse juridique satisfaisante n’a encore été trouvée pour les encadrer, alors que paradoxalement, la RSE donne naissance à des normes, des outils et des instruments pour les responsabiliser. L’étude de la responsabilité sociétale des entreprises transnationales à travers le prisme du droit révèle en réalité l’émergence d’un cadre de régulation hybride : les normes de RSE s’immiscent dans le droit, conduisant celui-ci à s’emparer de ces normes à son tour. Cet échange permet d’aborder l’entreprise transnationale à travers une approche nouvelle, tirée des normes de RSE, c’est-à-dire à travers son organisation et ses fonctions. Les relations de l’entreprise avec ses partenaires commerciaux deviennent alors une assise potentielle pour le droit, davantage que son statut ou que sa structure juridique, à partir desquelles peuvent être imputées des obligations, aujourd’hui inexistantes. Une fois l’entreprise transnationale saisie, c’est un cadre juridique adapté à son organisation complexe qui peut être mis à jour. L’étude des normes de RSE dévoile un enrichissement des règles applicables à l’entreprise transnationale et un renforcement potentiel de sa responsabilité juridique, fondée sur une approche préventive mais également solidaire du droit de la responsabilité. Passant outre les problèmes posés par l’absence de statut juridique, la RSE permet de saisir les entreprises transnationales par le biais de leurs relations commerciales, et d’envisager la conception d’un nouveau standard juridique de conduite sociétale, générateur d’une responsabilité individuelle et collective fondée sur une obligation de vigilance. Companies are now at the heart of global trade. These economic exchanges result in the establishment of commercial relationships, from which may emerge structures that are often complex and difficult to grapple with under the law: transnational corporations. While no satisfactory legal framework has yet been established to frame their work, paradoxically CSR gives rise to standards, tools and instruments to ensure their accountability. The study of the social responsibility of transnational corporations through the prism of the law actually reveals the emergence of a hybrid framework of regulation: CSR standards influence the law, forcing the law in turn to take note of these standards. This exchange allows us to handle a transnational business through a new approach derived from CSR standards, essentially through its organisation and functions. The relationship between a company and its business partners then becomes a potential basis for the law, rather than its status or its legal structure, from which can be derived responsibilities. Once a transnational corporation is seized, a legal framework adapted to its complex structure can come to light. The study of CSR standards reveals an enrichment of the rules applicable to transnational corporations and a potential strengthening of their legal liability, based on a preventive and joint and several approach of the law of responsibility. Ignoring the problems posed by the lack of legal status, CSR allows for the regulation of transnational enterprises through their commercial relations and provides a basis for the development of a new legal standard of social conduct, giving rise to individual and collective liability based on a duty of care.
Keywords: Accord-cadre international; Autonomie juridique; CSR; Code de conduite; Code of conduct; Collective labour relations; Conflict of laws; Conflit de lois; Conflits de juridiction; Corporate governance; Corporate veil of legal personality; Devoir de vigilance; Diligence; Droit du travail; Droits de l’Homme; Due diligence; Duty of care; Employment law; Entreprise; Entreprises multinationales; Gouvernement d'entreprise; Group of companies; Groupe de sociétés; Human rights; International Framework Agreement; Jurisdictional disputes; Labour law; Legal autonomy; Normes; Outsourcing; Precaution; Prevention; Précaution; Prévention; RSE; Regulation; Relations collectives de travail; Responsabilité sociétale; Responsabilité sociétale des entreprises multinationales; Régulation; Sous-traitance; Standards; Voile de la personnalité juridique

The primary importance of corporate social responsibility and ethicality in corporation reputation: an empirical study - Walker, Kent; Dyck, Bruno (Business and Society Review, 2014)
We examine three assumptions commonly held in the corporate reputation literature: i) reputation ratings of owners and investors are generally representative of all stakeholders; ii) stakeholders will generally provide a higher reputation rating to firms that emphasize corporate social responsibility versus firms that do not; and iii) profitability is the primary criterion of importance to all stakeholders when rating a firm’s reputation. Using an exploratory in-class exercise our findings suggest that: i) there are significant differences among stakeholder groups in their reputation ratings; ii) firms that emphasize corporate social responsibility are not rated more highly across all stakeholder groups, and iii) for all stakeholder groups, the ethicality criterion explained more of the variance in firms’ reputation ratings than the profitability criterion.
Keywords: CSR; Corporate Reputation; Corporate Social Responsibility; Criteria; Ethics; Profitability; RSE; Stakeholders

Corporate Social Responsibility (CSR) in the OHADA Law - Diawara, Karounga; Lavallée, Sophie (Journal of Business Law and Ethics, 2014)
CSR refers primarily to a framework idea according to which a corporation is encouraged, if not obliged, to go beyond the speculative and economic goals that benefit its members only, in order to integrate, into its decision-making process, other more holistic considerations of an ethical, social and environmental nature for the benefit of all stakeholders. CSR is a key concept that attempts to reconcile economic objectives with social, ethical and environmental considerations, with the particularity of questioning interactions between a corporation and its societal, ethical and ecological environment. This paper has a modest, but not uninteresting, objective. First, it offers an exploratory study that sets out markers for a more exhaustive analysis of the potential for CSR in the field of law in the Ohada zone. Our study is intended to be both theoretical and pragmatic: it asks questions and suggests topics for review from a normative standpoint largely inspired by socio-economic analysis. One of the interesting features of our approach is to consider, comprehensively, a complex notion that reflects several different concerns and is crossed by various conceptual frameworks that must be re-read in an “enlightened” manner, to see how it could potentially be made operational as part of Ohada law. This previously unexplored approach could lead, in time, to the establishment of a transnational committee on CSR in the Ohada zone.
Keywords: CSR; RSE

La responsabilité sociale de l’entreprise (RSE) dans l’espace OHADA : pour une ouverture aux considérations non économiques - Diawara, Karounga; Lavallée, Sophie (Revue internationale de droit économique, 2014)

Essays on corporate social responsibility and socially responsible investment - Lapointe, Vincent (Aix-Marseille Université, 2013)
Notre thèse traite des thématiques de la responsabilité sociétale des entreprises (RSE), de sa relation avec la performance économique et financière de l’entreprise, et de l’investissement socialement responsable (ISR). Ces thématiques ont récemment gagné en popularité, favorisées par un contexte de crise économique et environnementale. Notre thèse se compose de quatre principaux chapitres. Notre premier chapitre est une revue de la littérature académique sur la RSE et l’ISR. Nous proposons une revue interdisciplinaire de la littérature académique partagée entre l’économie et les sciences de gestion (éthique appliquée aux entreprises, stratégie et finance). Notre second chapitre est une analyse empirique de la relation entre RSE et performance financière de l’entreprise sous l’angle du coût du capital. Nous nous intéressons à l’impact de la publication d’une notation de la politique de RSE d’une entreprise sur la liquidité de ses titres et la taille de sa base d’actionnaires. Nos troisième et quatrième chapitres sont des analyses des propriétés de portefeuilles d’ISR construits à l’aide de nouvelles méthodes d’allocations. Ainsi nous analysons comment des stratégies d’allocations basées sur le risque modifient la performance des portefeuilles d’actifs financiers émis par des émetteurs ayant une politique de RSE, et réciproquement comment un univers d’investissement composé uniquement d’émetteurs ayant une politique de RSE modifie les propriétés de ces allocations alternatives.
Keywords: Alternative allocation strategies ("smart beta"); Base des investisseurs; CSR; Corporate Social Responsibility; Cost of equity capital; Coût du capital; Diversification; Efficience (gestion); Investissement socialement responsable; Investissements éthiques; Investor base performance; Liquidity; Liquidité; Matrice de covariance robuste; Performance; RSE; Responsabilité sociétale; Responsabilité sociétale de l’entreprise; Robust covariances matrix; Socially responsible investment; Stratégies d’allocation alternatives ("smart beta")

Activité agricole et pollution de l'eau : vers une responsabilité environnementale des exploitants agricoles ? - Pelzer, Stéphane (Université de Lorraine, 2013)
L'activité agricole est, depuis toujours, une source de pollution pour l'eau. Ce lien s'est intensifié avec la mise en place d'une Politique agricole commune à l'échelle de l'Union européenne. En effet la Politique agricole commune s'est construite sur le productivisme en optimisant le rendement des terres, notamment par l'utilisation d'intrants chimiques et naturels, ce qui fut particulièrement préjudiciable pour la ressource hydrique. Cependant, un certain nombre de réformes ainsi qu'une législation et une fiscalité spécifiques se sont érigées dans le but de limiter les effets néfastes de l'agriculture sur la ressource hydrique ; or ces instruments juridiques et institutionnels se sont avérés peu efficaces. Dès lors, les pouvoirs publics se sont employés à responsabiliser les auteurs de telles pollutions à travers un régime de responsabilité approprié. En dépit de ces efforts, le caractère diffus de la pollution de l'eau a constitué un obstacle majeur à l'application d'un tel régime aux pollutions d'origine agricole. Aussi, les pouvoirs publics n'ont d'autre choix que celui de se tourner vers des instruments juridiques plus souples qui permettent d'associer le pollueur aux différentes mesures de lutte contre la pollution de l'eau, notamment à travers la participation et la contractualisation.
Keywords: Activité agricole; Contrat environnemental; Directive cadre; Environnement (responsabilité); Fiscalité environnementale; Fiscalité écologique; Nitrates; Pays de l'Union européenne; Politique agricole commune; Politique de l'environnement; Pollueur-payeur; Pollution de l'eau (responsabilité); Pollution hydrique; Produits phytosanitaires; Responsabilité environnementale

Commerce équitable, développement durable : approche juridique - Matringe, Bovy (Université Montpellier 1, 2013)
Face aux effets néfastes de la croissance économique mondiale, la société civile réclame un autre développement, qui a été dénommé "développement durable" et défini dans le rapport Brundtland de 1987. Engagée dans l'Agenda 21, la France s'efforce d'adopter des textes législatifs et réglementaires pour promouvoir le développement durable. La charte de l'environnement de 2004 a été intégrée dans le préambule de la Constitution de 1958, conférant au développement durable un statut d'objectif à valeur constitutionnelle. Par l'article 60 de la loi du 2 août 2005, le commerce équitable s'inscrit dans la stratégie nationale de développement durable. Mais, aucune définition du commerce équitable ne figure dans cet article. Actuellement, les acteurs économiques pratiquent leur propre équité pour mettre en œuvre les conditions du commerce équitable. Celles-ci sont notamment le commerce avec les petits producteurs des pays du Sud, une production respectant l'environnement, le paiement d'un juste prix, ainsi que l'attribution de bénéfices sociaux aux producteurs et à leur famille. Les acteurs économiques établissent des attestations de qualité pour garantir aux consommateurs le respect de ces principes. D'un point de vue juridique, des questions se posent du fait que ces attestations ne sont ni initiées ni validées par les pouvoirs publics en France ou à l'étranger. La fiabilité de ces pratiques menace l'ordre juridique lorsque leur véracité ne peut pas être vérifiée. L'intervention de l'État est indispensable pour légiférer sur l'équité en question. Néanmoins, un État ne représente que l'intérêt de son peuple sans pouvoir faire d'ingérence dans les affaires d'un autre État souverain, alors que la législation du commerce équitable implique une gouvernance des relations commerciales entre les acteurs économiques des pays du Nord avec les petits producteurs des pays du Sud. En conséquence, il va falloir trouver un nouveau mode de gouvernance pour réguler le commerce équitable. M. Pascal LAMY appelle cette nouvelle gouvernance "gouvernance alternationale". Pour la réaliser, la participation de la société civile à côté de celle des pouvoirs publics est nécessaire.
Keywords: CSR; Certification; Commerce équitable; Competencia; Competition; Competition law; Concurrence (droit); Droit; Droit de la consommation; Droit de la propriété intellectuelle; Développement durable; Ethic; Fair trade; Justice; Morale; RSE; Responsabilité sociétale; Sustainable developpement; Éthique des affaires

Commerce équitable, développement durable : approche juridique - Sok, Bovy (Université Montpellier 1, 2013)
Face aux effets néfastes de la croissance économique mondiale, la société civile réclame un autre développement, qui a été dénommé " développement durable " et défini dans le rapport Brundtland de 1987. Engagée dans l'Agenda 21, la France s'efforce d'adopter des textes législatifs et réglementaires pour promouvoir le développement durable. La charte de l'environnement de 2004 a été intégrée dans le préambule de la Constitution de 1958, conférant au développement durable le statut d'objectif à valeur constitutionnelle. Par l'article 60 de la loi du 2 août 2005, le commerce équitable s'inscrit dans la stratégie nationale de développement durable. Mais, aucune définition du commerce équitable ne figure dans cet article. Actuellement, les acteurs économiques pratiquent leur propre équité pour mettre en œuvre les conditions du commerce équitable. Celles-ci sont notamment le commerce avec les petits producteurs des pays du Sud, une production respectant l'environnement, le paiement d'un juste prix, ainsi que l'attribution de bénéfices sociaux aux producteurs et à leur famille. Les acteurs économiques établissent des attestations de qualité pour garantir aux consommateurs le respect de ces principes. D'un point de vue juridique, des questions se posent du fait que ces attestations ne sont ni initiées ni validées par les pouvoirs publics en France ou à l'étranger. La fiabilité de ces pratiques menace l'ordre juridique lorsque leur véracité ne peut pas être vérifiée. L'intervention de l'État est indispensable pour légiférer sur l'équité en question. Cependant, un État ne représente que l'intérêt de son peuple sans pouvoir faire d'ingérence dans les affaires d'un autre État souverain, alors que la législation du commerce équitable implique une gouvernance des relations commerciales entre les acteurs économiques des pays du Nord avec les petits producteurs des pays du Sud. En conséquence, il va falloir trouver un nouveau mode de gouvernance pour réguler le commerce équitable. M. Pascal LAMY appelle cette nouvelle gouvernance " gouvernance alternationale ". Pour la réaliser, la participation de la société civile à côté de celle des pouvoirs publics est nécessaire. Social society claims for the sustainable development against the nefas effect of the world economic growth. In 1987, the sustainable development is, officially, announced in the Brundtland report. Engaged by the Agenda 21, France gets to promote the sustainable development by creating laws and government acts. Indeed, the environmental Charter year 2004 is integrated into the preamble of the French Constitution year 1958. The sustainable development is considered as a goal within constitutional value. With article 60 of the law released on 2nd of August 2005, fair trade is registered as the national strategy for the sustainable development. Without any legal definition on fair trade, the economic actors introduce their own equity to run the fair trade conditions. They are for example practice of fair trade with the disadvantage farmers or producers in South, payment of fair price, social welfare respect and environmental respect. Some main economic actors run the quality acknowledgement as the proof of compliance with the fair trade conditions. Actually the quality acknowledgement doesn't get approved by France or any governments in the world. Lack of the juridical instruments to verify the reality of fair trade quality becomes a danger for the juridical order. The government intervention is required to set up the order for fair trade practices. But, an independent government represents, legally and only, their own citizens. Or, the legislation on fair trade needs the management of the trade operated between the economic actors in North and the small producers in South. That's a reason of seeking a new model of governance to regulate fair trade. Mr. Pascal LAMY calls for the alternational governance which needs the participation of the social society among the governments.
Keywords: Abus de position dominante; Attestation; Bien commun; Bien mondial; Bien public; CSR; Certification; Charte; Chose commune; Code de conduite; Commerce équitable; Concurrence; Consommation; Droit économique; Développement durable; Entente; Environnement; Equité; Ethique; Gouvernance; Juste prix; Justice; Label; Marché public; Marque; Mondialisation; Morale; Partenariat public-privé; Pays du Nord; Pays du Sud; Pratique trompeuse; Prime pour le développement durable; Propriété intellectuelle; Préfinancement; Qualité; RSE; Responsabilité sociale des entreprises; Référentiel; Transparence; subsidiarité

La responsabilité sociétale des entreprises et la médiation - Mattei, Laetitia (Université Paris 9, 2012)
Les crises actuelles, sous leurs multiples aspects, mettent en lumière la responsabilité des entreprises dans notre société, bousculant ainsi l'un des dogmes néolibéraux résumé par la célèbre formule de Milton Friedman (1970) : « La responsabilité sociétale de l’entreprise est d’accroître ses profits». C’est en réaction à ces crises et grâce au rôle actif de la société civile qui condamne désormais certaines pratiques, que le concept de responsabilité sociétale des entreprises (ci-après RSE) a émergé. L’enjeu est donc, aujourd’hui, de mettre en place un marché responsable entre l’entreprise et ses parties prenantes. Le législateur, par la loi Grenelle I, dispose que la médiation sera un des outils de mise en oeuvre de la RSE. Il en appelle donc au développement du droit processuel qu’est la médiation pour mettre en oeuvre ce droit substantiel qu’est la RSE. La médiation, à la fois préventive et curative, est donc un outil de mise en oeuvre de la RSE. Le couple RSE et médiation permet ainsi de combiner efficacité économique, respect social,sociétal et environnemental
Keywords: Company; Entreprise; Grenelle Environnement 2007; Législation; MARD; Mediación; Mediation; Mediação; Médiation; Paris; Parties prenantes; Parties prenantes (gestion d'entreprise) -- France; Procédure (droit); Responsabilité; Responsabilité sociétale; Responsibility; Sociétal; Stakeholders

Nigeria, oil and gas exploration and the Niger delta question : a study in corporate social responsibility - Bribena, E. K. (North-West University, 2011)
This thesis addresses issues of the Niger Delta question which represents one of the most intractable sources of socio-political destabilization in the Niger Delta region of Nigeria. The study is on the intricate dynamics amongst the Nigerian state, the transnational oi l corporations, the oil producing communities and the insurgent militia conflict. It investigates and explicates the "paradox of plenty" and the "resource curse", the "absentee government" and "state capture" and the debilitating effects of petroleum politics in Nigeria. The economic exploitation of the Niger Delta region's vast crude oil reserves by transnational oil corporations and government authorities is juxtaposed with the spectre of environmental degradation, human rights violations, and the recurrent rule of impunity. The protracted problems of the Niger Delta region thus, provide us with a pertinent analytical and contextual framework for the study of the dynamics and issues of transparency in other African petro-dollar states. It is argued in this study that the Niger Delta crisis is a conflict of values and fight for resources arising from decades of unacceptable standards of oil exploration and the absentee character of the Nigerian State. By its very nature, the study called for a qualitative approach, supplemented by unstructured interviews using aide memoirs with selected officials, on the basis of their innate knowledge of the subject matter. The legal comparative research method, with a historic component also played an integral role in this study. Some key findings and conclusions: 1. The study found that the Niger Delta crisis graduated from mère political agitations for state creation and provision of social amenities to extreme acts of hostage-taking and a twist of violence as a result of treating a major problem affecting the development of the Niger Delta people with levity for too long a period. 2. The study found that the on-going crisis in the Niger Delta region of Nigeria is a conflict of values and fight for resources amongst the oil-bearing people of the Niger Delta, transnational oil corporations and the Nigerian Government. 3. The study established some causal nexus between oil and poverty; oil and corruption; and, oil and human rights abuses. 4. That, the Niger Delta crude oil conflict is essentially a manifestation of state capture and inertia on the part of the Nigerian Government. 5. The study found that the Niger Delta economies are "criminalized" and are often characterized by conditions of anarchy and impunity. And this disorder is embedded in the dynamics of resource extraction, the nature and role of "shadow" state actors, as well as the interplay and patterns of relationships between organized criminal syndicates and the transnational oil corporations in the host communities. The study recommends, inter alia: I. That steps be taken by government to re-define its philosophy of national economic development from a state-driven to citizens-driven philosophy. To this end, Nigeria must seek to develop by developing its citizens, the aggregate of whose satisfactory living conditions should form the criteria for measuring national development. II . That effort must be made to steer the nation towards proper fiscal federalism. The present "food is ready" economy whereby federating units are enslaved to national "cake sharing" instead of value generation, discourages entrepreneurship and sustainable development. It promotes undue dependency on petroleum products, inequity and ethnic distrust. Ill. That Nigeria needs productive resource control, not just development in the sense of house and bridge building. What is needed is a noticeable leap in the standard of living in the Niger Delta. Thus, people and not federal accounts must be the object of improvement. IV. It is recommended that government should ensure robust, independent and co-ordinated oversight of the oil industry including its impact on human rights. V. Transnational oil corporations should undertake full corporate social responsibility and comprehensive assessment of the social and human rights impacts of all oil and gas projects, ensuring that adequate information is provided to affected individuals and communities and that the process is transparent. VI. It is strongly recommended that an Oil Pollution Liability Trust Fund should be established by the Federal Government in concert with oil companies. The fund will be made up of a percentage of tax levied on oil companies and a percentage of earnings of the Federal Government from oil. The fund should be used in ameliorating the conditions of the impacted environment and people. It is hoped that these findings and recommendations will go a long way in the quest for significant environmental and social improvements in the Niger Delta region of Nigeria.
Keywords: CSR; Corporate Social Responsibility; Nigeria; Petroleum industry and trade

Exploring the limits of Western Corporate Social Responsibility Theories in Africa - Dartey-Baah, Kwasi; Amponsah-Tawiah, Kwesi (International Journal of Business and Social Science, 2011)
Corporate Social Responsibility (CSR) is about the relationship of organisations with society as a whole, and the need for organisations to align their values with societal expectations. Generally, CSR practice in Africa is thought to be adopted from Western business theories although there is evidence to suggest that Western CSR theories are not totally applicable in Africa. This is due to differences in drivers or causes of CSR in the West and in Africa, as well as cultural and managerial traits in Africa. This paper explores the limits of Western CSR Theories in Africa and argues that improved ethical responsibilities, incorporating good governance should be assigned the highest CSR priority in developing countries. It further adds that increased legislation, change in CSR priorities and the application of indigenous CSR theories such as Ubuntu, African Renaissance and Omuluwabi are means of countering the limits of Western CSR theories in Africa. Keywords: CSR, Western CSR Theory, Africa, Ubuntu, African Renaissance, Omuluwabi
Keywords: Africa; CSR; RSE; Renaissance; Ubuntu; Western CSR Theory

المعايير الدولية لمكافحة الإتجار بالأشخاص وانسجامها مع القوانين الوطنية - حطاب, عبد النور (Ibn Khaldun University of Tiaret, 2011)
لقد حاولنا ومن خلال هذه الدراسة أن نوضح كيف تصدى المشرع الدولي لأفعال الاتجار بالأشخاص، من خلال استعراض عدد من الاتفاقيات الدولية العامة والخاصة منها و الصكوك الدولية الإقليمية لمكافحة هذه الظاهرة وحددنا أهم الالتزامات التي رتبها على الدول في هذا الشأن. أما على المستوى الوطني فقد تعرضنا لإدماج المعاهدات الدولية في التشريع الوطني و للمعايير التي يتعين على الدول إنفاذها داخل تشريعاﺗﻬا الوطنية وفاءا منها بالتزاماﺗﻬا الدولية وحددنا وسائل تنفيذ السلطات الوطنية لالتزاماﺗﻬا الدولية ومن أهم تلك الوسائل إصدار التشريعات الوطنية التي تحظر الاتجار بالأشخاص وتعاقب عليه.وقد كان المشرع الوطني في الجزائر سباقا في إعمال نصوص الاتفاقيات الدولية داخل التشريع الجزائري، فأصدر تعديل لقانون العقوبات ضمنه قسم خاص بمكافحة الاتجار بالأشخاص وفقا للمعايير الدولية السارية في هذا الشأن.
Keywords: Accords bilatéraux; Crime organisé; Normes internationales; Traite des esclaves; Traite des êtres humains